2012
DOI: 10.1155/2012/586589
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in Pain Outcomes in a Canadian Pediatric Teaching Hospital Following Implementation of a Multifaceted, Knowledge Translation Initiative

Abstract: Following KT initiatives, significant improvements in pain processes (pain assessment documentation and pain management interventions) and clinical outcomes (pain prevalence, pain intensity) were observed. Further improvements are recommended, specifically with respect to procedural pain practices and opioid utilization patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 28 publications
1
31
1
3
Order By: Relevance
“…The 63% adherence rate among participating nurses is comparable to rates reported for the documentation of pain assessment in hospitalized patients, which ranges from 63% to 83% in published studies. 2125 The study most closely comparable to ours, in that it examined pain ratings on nurse-completed admission forms in a general adult hospital population, reported a rise in documentation from approximately 56% to 63% after the introduction of a year-long pain care improvement program. 24 …”
Section: Discussionsupporting
confidence: 63%
“…The 63% adherence rate among participating nurses is comparable to rates reported for the documentation of pain assessment in hospitalized patients, which ranges from 63% to 83% in published studies. 2125 The study most closely comparable to ours, in that it examined pain ratings on nurse-completed admission forms in a general adult hospital population, reported a rise in documentation from approximately 56% to 63% after the introduction of a year-long pain care improvement program. 24 …”
Section: Discussionsupporting
confidence: 63%
“…HCPs' correct answer rate to questions related to this group of patients was the lowest. Likewise other studies described the ill preparation of HCPs to assess and manage children's pain [15, 16, 27, 50, 54, 55]. …”
Section: Discussionmentioning
confidence: 99%
“…Aghaei Hashjin et al reported an improvement in the performances of hospitals in Iran following implementation of a performance measuring program [57]. Moreover, auditing and monitoring coupled with education improved pain assessment and management in Canadian paediatric hospital [55]. In addition, public hospitals are larger, with higher patient traffic and a more stressful environment, which reflects the need to create and implement adequate clinical training courses in these hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the documentation of nonpharmacological interventions may be underestimated (Zhu et al . , Harrison et al . ).…”
Section: Discussionmentioning
confidence: 99%